Correction of distorted 3-D images for misalignment of an optical structure in a multiview 3-D display system - Kwon, Yongjoon; Kim, Donghwan; Kim, Sung-Kyu (SPIE-SOC PHOTO-OPTICAL INSTRUMENTATION ENGINEERS, 2018)
For a multiview three-dimensional (3-D) display system using a two-dimensional (2-D) flat panel display, it is very important to attach accurately an optical plate such as a parallax barrier and a lenticular lens sheet onto a 2-D display panel for the best quality of 3-D images. In most practical cases, however, misalignment occurs since it is too difficult to align perfectly in assembly process. In general, angular misalignment results in the deterioration of 3-D image quality by some increase of crosstalk, so that the resulting 3-D images are even distorted as tilted ones. To correct distorted 3-D images, we propose a method to skew 3-D objects before each image for multiviews is taken by multiple cameras. For this, a formula is derived to determine the amount of skewing 3-D objects. And by using it, some experimental results are shown that distorted 3-D images in a misaligned multiview 3-D display system are completely corrected. Since skewing 3-D objects implies a coordinate transformation of 3-D space, this method can be also used in the manipulation of 3-D image data obtained from a depth camera in order to correct the distorted 3-D images caused by angular misalignment. (C) The Authors. Published by SPIE under a Creative Commons Attribution 3.0 Unported License.
Keywords: AUTOSTEREOSCOPIC 3D DISPLAYS; LENTICULAR DISPLAYS; TECHNOLOGIES; CALIBRATION